Value Innovation: The New Source Of Sustainability - Hajar, Mohammed A.; Daing Nasir, Ibrahim; Mohd Ridzuan, Darun
In today’s highly competitive business environment, innovation per se may not be sufficient enough to sustain long-term success and competitive advantage. Innovation protection has become difficult without dynamic process of value innovation that can open new market spaces, make the competition irrelevant and create valuable intangible resources including firm’s reputation (customer satisfaction) and brand loyalty (customer loyalty). This paper aims to provide a new perspective to approach sustainability through value innovation in the Resource-Base View (RBV) context. This study highlights the new strategy of market transformation from physical tangible assets to value-creating intangible assets by presenting three innovation cases. In particular, this paper can motivate corporation to focus on value innovation rather than beating the competition in order to create a leap in value for both customers and themselves. Thus, this paper suggests a conceptual framework to enhance customer satisfaction and promotes customer loyalty in order to achieve competitive advantage, and hence sustainability.